(untitled) (Al-Qamar, 2022)
The translation is an “exact art” an “inexact science” and a set of superior linguistic and interpretative skills, based on linguistic and cultural erudition. It is a fact that English writers had proven themselves godfathers in this field by introducing and making Translations as knowledge rather than an art only. This article explores alternative interpretations of divine texts and develops their potential to reinforce the Quran’s inclusive nature which promotes equality and freedom of choice and finding the key notion of translation equivalence and definition and reviews of background concepts relevant to Islamic and divine text translation theories and methods by different English writers. Chief among them are the models of translation (such as ST/TT oriented translation), the text-linguistic model, and the text type-oriented translation model.